1993
DOI: 10.1007/bf00299446
|View full text |Cite
|
Sign up to set email alerts
|

Paralysis of the arm after posterior decompression of the cervical spinal cord

Abstract: Paralysis of the arm with radicular distribution occurring after posterior decompression of the cervical spinal cord included C5, C6, C7 and C8 roots, in isolation or combined. The most frequent patterns of paralysis were C5 and C6 root involvements of the motor-dominant type. The overall frequency of occurrence in our series was 11% (20 cases of postoperative paralysis in 188 surgical cases), but the frequency varied with the posterior decompression method. The higher frequency of postoperative paralysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 2 publications
1
48
0
Order By: Relevance
“…Tsuzukil et al [26] noted that a smaller laminar opening might suppress posterior shift of the dural tube. Such suppression with balanced traction forces on the bilateral roots might reduce the traction effect of the bulging dural tube on the roots, which can prevent postoperative C5 root injury.…”
Section: Optimal Los Following Odclmentioning
confidence: 99%
“…Tsuzukil et al [26] noted that a smaller laminar opening might suppress posterior shift of the dural tube. Such suppression with balanced traction forces on the bilateral roots might reduce the traction effect of the bulging dural tube on the roots, which can prevent postoperative C5 root injury.…”
Section: Optimal Los Following Odclmentioning
confidence: 99%
“…In 1972, the idea of cervical laminoplasty was first introduced by Oyama and coworkers [1] by the name of ''Expansive lamina-Z-plasty'' to decrease these complications by preserving the posterior osseous structures of the cervical spine as much as possible. Thereafter, various methods of cervical laminoplasty have been developed in Japan [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the surgical methods of cervical laminoplasty are broadly divided into two types from the viewpoint of the site of osteotomy: open-door type [2,3,6] and double-door type [4,5]. In the open-door type, osteotomy is performed at one side of the lamina-facet junction.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the C-5 segment is usually the point at which the extent of posterior shift of the cord is greatest. Using cadavers, Tsuzuki et al 32,33 demonstrated that impingement of the nerve root occurs inside the uncovertebral joint with backward shifting of the spinal cord after laminoplasty.…”
Section: Discussionmentioning
confidence: 99%